2018
DOI: 10.1007/s10899-018-9813-8
|View full text |Cite
|
Sign up to set email alerts
|

Peer Group Identification as Determinant of Youth Behavior and the Role of Perceived Social Support in Problem Gambling

Abstract: Gambling opportunities have increased rapidly during recent years. Previous research shows that gambling is a popular activity among youth, which may contribute to problem gambling. This study examined how social identification with online and offline peer groups associates with youth problem gambling behavior and if perceived social support buffers this relationship. Data were gathered with an online survey with 1212 American and 1200 Finnish participants between 15 and 25 years of age. Measures included the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 84 publications
3
25
0
Order By: Relevance
“…As earlier highlighted by Holdsworth et al (2015), psychosocial factors may constitute risk and protective factors in themselves, they can be the result of problems related to gambling, and they can also have a mediating/moderating effect on the links between various factors and gambling or problem gambling through functioning as resiliency factors and in influencing coping (for example, social support). In the study by Savolainen et al (2019), no direct associations were found between social support and problem gambling, while social support moderated the association between peer group identification and problem gambling. Among Finnish young people, problem gambling was more common among those who strongly identified with an online peer group but experienced low social support.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…As earlier highlighted by Holdsworth et al (2015), psychosocial factors may constitute risk and protective factors in themselves, they can be the result of problems related to gambling, and they can also have a mediating/moderating effect on the links between various factors and gambling or problem gambling through functioning as resiliency factors and in influencing coping (for example, social support). In the study by Savolainen et al (2019), no direct associations were found between social support and problem gambling, while social support moderated the association between peer group identification and problem gambling. Among Finnish young people, problem gambling was more common among those who strongly identified with an online peer group but experienced low social support.…”
Section: Discussionmentioning
confidence: 70%
“…Another study (Oksanen et al, 2019), found that weaker social support from close people was associated with competent gambling among young Finns, while higher perceived social support was associated with entertainment gambling. In another Finnish study, no direct associations were found between social support from close people and problem gambling, while high levels of social support did moderate the association between peer group identification and problem gambling (Savolainen et al, 2019). On the other hand, Fröberg et al (2013) did not find social support to be associated with gambling among young Swedes, and Nordmyr et al 2016did not find social support to be associated with problem gambling in a Finnish sample.…”
Section: The Collected Quantitative Evidence On Experienced Social Sumentioning
confidence: 92%
See 1 more Smart Citation
“…Perceived social support can improve their self-efficacy [54], positively relate to social goal pursuit [56] and influence life satisfaction [57,58] and well-being [59,60]. Individuals with higher perceived social support are more likely to engage in group activities [61] and have a more robust group identification [62].…”
Section: Perceived Social Supportmentioning
confidence: 99%
“…Similarly, majority (55.0%) of the students imbibed peer group's behaviours. In other words, the students were transformed by the attitudes of the peer groups, which is why Savolainen et al (2019) suggested that parents and teachers should properly guide the students by advising them on the types of peer groups to associate with at their adolescence stage, more especially those groups with negative behaviours. The finding of this research on peer group's transformation of members behaviour is consistent with the study of Huang et al (2014) who discovered that friends and adolescence risky behaviours are strongly corelated.…”
Section: Status Of Utilisation Of Information By Students In Peer Groupsmentioning
confidence: 99%